Savor you : a Fusion novel - Proby, Kristen (Proby, Kristen. Fusion series, 2018)
Cooking isn't what Mia Palazzo does, it's who she is. Food is her passion. She's built a stellar menu full of delicious and sexy meals for her restaurant, Seduction. Now, after being open for only a few short years, Mia's restaurant is being featured on Best Bites TV. TTo say Seduction is a wild success is an understatement. All the blood, sweat, tears, and endless hours of work Mia has put into the restaurant has finally paid off. Then Camden Sawyer, the biggest mistake of the life, walk into her kitchen...Camden's celebrity chef status is world-renowned. He's the best there is, and the kitchen is where he's most at home. He can't resist the invitation to Portland for a showdown against Mia for a new television show. Mia was in his life years ago, and just like before, he's met his match in the beautiful Italian spitfire. The way she commands the kitchen is mesmerizing, and her recipes are clever and delicious. He's never had qualms about competition, and this is no different. He can't wait to go head to head with Mia. But can he convince her the chemistry they share in the kitchen would be just as great in the bedroom as well? As Mia and Camden face off, neither realizes how high the stakes are as their reputations are put on the line and their hearts are put to the ultimate test.--Provided by Publisher.